An Error Analysis in Using Adjective Order at English Education Study Program Students of IAIN Manado - Halimah, Nur; Saini, Fadhlan; Gerace Tinangon, Windi (Universitas Islam Negeri Alauddin Makassar, 2023)
This study aims to determine the proportion (frequency and percentage) of errors and dominant errors in the composition of adjectives. This study focused on the analysis of misordering errors based on the Surface Strategy Taxonomy by Dulay in the use of adjective order. The research methodology in this study was a quantitative descriptive method. The respondents of this study were 20 second semester students of the English Education Study Program at the Manado State Institute of Islamic Studies with the academic year 2021/2022. The researcher used a test as an instrument to collect data. The following test was in the form of; Rearrange Words and Multiple Choices. In the meantime, the data analysis procedure applied in this study was collecting a sample, identifying error based on the sequence of adjectives by Frank theory, describing the results, and evaluating the errors. The research findings show that students at second semester of English Education Study Program have errors to identify the appropriate order of adjectives in the sentence. In addition, researcher found that there were 520 frequencies of misordering errors with an error percentage of 50.0%. Rearrange words test have 272 frequency of errors (52.3%) and Multiple Choices test have 248 frequency of error (47.7%). In short, the dominant error based on the test is Rearrange words, with a total misordering error which is 272 errors and its’ percentage 52.3%. The most dominant errors in adjective order item is Shape with a total frequency of 52 out of 80 total errors with 13% error percentage. The research implications is students can be aware in using more adjectives with correct ordering especially when use adjective shape.